Activated charcoal reduces pasture herbicide injury in vegetable crops. (March 2019) - Singh, Vijay; Masabni, Joseph; Baumann, Paul; Isakeit, Thomas; Matocha, Matthew; Provin, Tony; Liu, Rui; Carson, Katherine; Bagavathiannan, Muthukumar
Abstract: Vegetable producers are often concerned about potential herbicide carryover and injury to vegetables following the application of livestock manure/compost from animals fed with treated hay. A greenhouse study was conducted to evaluate the effect of activated charcoal on soil residual activity of the herbicides aminopyralid, aminocyclopyrachlor, and picloram, applied at recommended field rates of 120 g ae, 70 g ai, and 303 g ai ha −1 respectively, on tomato, okra, and cantaloupe. A commercial source of activated charcoal was used at four rates [0, 0.5X, 1X, and 2X (1X = 336 kg ha −1 )]. When no activated charcoal was applied, aminopyralid caused the greatest injury to tomato and okra, leading to plant death at 4 weeks after emergence/transplanting (WAE/T). At the highest rate (2X) of activated charcoal, crop injuries due to aminopyralid were reduced by 72 and 78% for okra and cantaloupe, respectively at 4 WAE, while tomato did not respond to the 2X rate of activated charcoal. For aminocyclopyrachlor, even a much lower rate (0.5X) of activated charcoal was sufficient to reduce about 70% of the injury caused on cantaloupe and okra. For picloram, activated charcoal application at the 2X rate reduced injury by 78–94% across the three vegetable species investigated. Under low herbicide residue levels that usually occur under carryover situations, a much lower rate of activated charcoal (<100 kg ha −1 ) may be sufficient and practically feasible. Overall, activated charcoal application shows promise for remediating soil contaminated with herbicide residues, but crop response can be variable and requires optimization for specific herbicide, species, and use scenarios. Highlights: Tomato was the most sensitive species to carryover from pasture herbicides, compared to okra and cantaloupe. Activated charcoal (AC) reduced injuries caused by aminopyralid, aminocyclopyrachlor, and picloram; greater injury reduction with higher rates. AC at a rate of 168 kg/ha was sufficient to remediate aminocyclopyrachlor injury but higher rates were required for aminopyralid and picloram. The remediation potential provided by activated charcoal application was influenced by application rate, herbicide, and vegetable species.